2003
DOI: 10.1144/gsl.sp.2001.211.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary architecture and post-glacial evolution of Cheekye fan, southwestern British Columbia, Canada

Abstract: The purpose of this paper is to examine the internal architecture and post-glacial evolution of Cheekye fan, British Columbia, Canada. Analysis of a large database of ground penetrating radar (GPR) profiles has allowed the identification of ten reflection configurations that characterize this high-energy environment. GPR profiles augmented with test-pit, well-log and radiocarbon data provided detailed subsurface information and revealed the large-scale internal architecture and Holocene sedimentation history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…More precipitation (increasingly in the form of rain at higher elevation) and more intensive rainfall could lead to an increase in debris-flow frequency, though arguable if this increase would also be manifested in an increase in debris-flow magnitude. Although mean annual precipitation increased sharply after about 6000 years ago, and climate mediated changes in debris-flow magnitude frequency have been postulated (Ekes and Friele, 2003;), we have not been able to detect a clear signal that would indicate a change of debris-flow activity in the Cheekye River watershed as a result of climate change effects.…”
Section: Climate Change Scenariocontrasting
confidence: 67%
See 2 more Smart Citations
“…More precipitation (increasingly in the form of rain at higher elevation) and more intensive rainfall could lead to an increase in debris-flow frequency, though arguable if this increase would also be manifested in an increase in debris-flow magnitude. Although mean annual precipitation increased sharply after about 6000 years ago, and climate mediated changes in debris-flow magnitude frequency have been postulated (Ekes and Friele, 2003;), we have not been able to detect a clear signal that would indicate a change of debris-flow activity in the Cheekye River watershed as a result of climate change effects.…”
Section: Climate Change Scenariocontrasting
confidence: 67%
“…From this, a suite of 10 radar facies were developed, representing subfan bedrock and till, subaqueous deltaic (foresets), subaerial alluvial fan (sheetflood and debris flow), and Squamish River floodplain depositional settings. An architectural model for the lower Cheekye fan developed from GPR surveys (Ekes and Friele, 2003) concluded that the subaerial package was divisible into two radar facies: one unit characterized by undulating to hummocky reflectors and found at depth and near the fan apex; and the second unit with mainly planar reflectors found near the surface and at the margins of the fan. Surface exposures suggest that the first unit is composed of matrix-rich debris-flow deposits and the second unit consists of clast-rich debris flow, hyperconcentrated flow, and channel lag deposits.…”
Section: Chronology Of Cheekye River Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, numerous authors speculate about climatic and tectonic controls on depositional patterns of alluvial fans (e.g. Blair and McPherson, 1995;Blair, 1999;Èkes and Friele, 2003), absolute, unambiguous stratigraphic data are lacking to verify their models of fan architecture. These models are based on properties of the fan surface, one-dimensional qualitative observations at outcrops and theoretical models of sediment distribution.…”
Section: Introductionmentioning
confidence: 99%
“…GRU 2 is interpreted as deposits of FA 1. Continuous, horizontal to subparallel, and in places hummocky reflections sharply truncating underlying inclined reflections of foreset are typical of fluvial topsets of Gilbert deltas in GPR cross sections (Jol & Smith 1991), and are generally also characteristic for alluvial horizontally bedded sands and gravels (Ékes & Friele 2003). GRU 3 is compared with FA 2.…”
Section: Ground Penetrating Radarmentioning
confidence: 99%